1993
DOI: 10.1007/bf00872389
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic karyotyping as a taxonomic tool in the genusSaccharomyces

Abstract: The electrophoretic karyotypes of strains of the ten species of the yeast genus Saccharomyces (sensu Vaughan-Martini & Martini 1992) were determined by the CHEF (contour-clamped homogeneous electric field) system of pulsed field gel electrophoresis. The number of bands was found to vary from 6 to 17 and the calculated molecular weights of haploid genomes ranged from 7.9 to 14.6 Mbp. The type strains of S. exiguus and the four species of the Saccharomyces sensu stricto complex (S. bayanus, S. cerevisiae, S. par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
72
1
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 28 publications
10
72
1
1
Order By: Relevance
“…Previous studies have shown that the species of Saccharomyces sensu stricto exhibit relatively homogeneous karyotypes compared with those of species of Saccharomyces sensu lato (Vaughan-Martini et al, 1993;Fischer et al, 2000;Naumov et al, 1992Naumov et al, , 1995Petersen et al, 1999;Lu et al, 2004;Wu & Bai, 2005). The electrophoretic karyotypes of strains H-6 T , ZX-15 and ZX-20 bore a superficial resemblance to those of the accepted Saccharomyces species, being consistent with their placement in this genus based on rDNA sequence analysis (Fig.…”
Section: Electrophoretic Karyotypingsupporting
confidence: 65%
“…Previous studies have shown that the species of Saccharomyces sensu stricto exhibit relatively homogeneous karyotypes compared with those of species of Saccharomyces sensu lato (Vaughan-Martini et al, 1993;Fischer et al, 2000;Naumov et al, 1992Naumov et al, , 1995Petersen et al, 1999;Lu et al, 2004;Wu & Bai, 2005). The electrophoretic karyotypes of strains H-6 T , ZX-15 and ZX-20 bore a superficial resemblance to those of the accepted Saccharomyces species, being consistent with their placement in this genus based on rDNA sequence analysis (Fig.…”
Section: Electrophoretic Karyotypingsupporting
confidence: 65%
“…Some species show remarkably stable karyotypes (Boekbout & Bosboom 1991;Vaughan Martini et al 1993). The occurrence of chromosomal length polymorphisms may allow fingerprinting of strains which may benefit epidemiology and the establishment of proprietary rights.…”
Section: Discussionmentioning
confidence: 99%
“…Because the 41 S. cerevisiae strains can be thought of as one species with regard to the set of probes to which they are able to hybridize, while each of the six non-cerevisiae species is expected to hybridize only to its own set of probes, we adjusted the amount of DNA for all 41 S. cerevisiae strains taken together to be approximately equal to the amount of DNA for each of the single other species. This approach gave a pool with essentially equimolar amounts of each species' genome, because the haploid genome sizes of all seven Saccharomyces species are very similar (Vaughan-Martini et al 1993). As a test, the reference sample pool was labeled and hybridized in both single color (Cy3 dye label only) and ''self-self hybridization'' two-color (Cy3 and Cy5) control experiments; as expected, the pool gave robust hybridization signals for almost every spot on the microarray and was therefore used as the ''reference'' sample for all subsequent experiments (data not shown).…”
Section: Acgh Protocol Using Multispecies Arraysmentioning
confidence: 99%